Primary Response and Concern of Sabah’s Geopark Potential Economic Effects: Preliminary Study - Rafiq Idris; Kasim Mansur (2020)
Sabah, Malaysia is moving steps forward by announcing the gazettement of some areas as geoparks. Part of the areas include the district of Ranau, Kota Marudu and Kota Belud. Some of the areas involved if not all are under a national park program prior to this. This gazettement undoubtedly has the potential to bring economic benefit to the state. It has the potential to increase land value, stimulating economic activities especially in the services sector via tourism activities, enhancing protection for environment and as a mean to control aggressive use of land for development. On the other hand, there are some concerns of stakeholders. Issues such as potential restriction for farmers to do agriculture related activities and relocation of village among others are potential concern among communities in Ranau, Kota Marudu and Kota Belud. In this regard, in order to examine the real concerns of various stakeholders, some series of roundtable discussions and interviews have been undertaken. Based on the preliminary assessment, very small number of individuals have worry about the geopark idea. Majority look at it positively.